Recent Progress in Optically-Active Phthalocyanines and Their Related Azamacrocycles - Okada, Yusuke; Hoshi, Tomonori; Kobayashi, Nagao (Frontiers in Chemistry, 2020)
Optically-active phthalocyanines (Pcs) and related macrocycles reported in the 2010-2020 period are introduced in this review. They are grouped into several categories: 1) chiral binaphthyl-containing Pcs, 2) optically active alkyl chain-containing Pcs, 3) chiral axial ligand- coordinated or -linked Pcs, 4) chiral subphthalocyanines (SubPcs), and 5) related azamacrocycles. For each compound, the structure and important characteristics are summarized.